The evaluation of two different surgical approaches in total hip arthroplasty according to the patient satisfaction, plantar pressure distribution and trendelenburg sign - Ahmet Yildirim; Tacettin Ayanoglu; Mustafa Ozer; Erdinc Esen; Ulunay Kanatli; Selcuk Bolukbasi (Medicine Science, 2019)
The aim of this prospective study was to analyze the results of two different surgical aproaches for total hip arthroplasty as Trendelenburg sign, plantar pressure distribution with the help of dynamic pedobarography and clinical results by Harris Hip Score. A total of 28 patients who underwent unilateral total hip arthroplasty using two different types of lateral approach as conventional lateral Hardinge approach and intermuscular Hardinge approach described by Pai were included in this study. Plantar pressures have maesured by EMED-SF pedobarography device and analysed by the help of a commercial software; that seperates the foot to the four different parts which are called masks. Trendelenburgs sign has been estimated as grade 1 and grade 2 by the method which was described by Hardcastle and Nade. Clinical outcome was measured by comparing Harris Hip Scores pre-operatively and postoperatively at last clinic visit. In both groups after the two years from the surgery; total contact time has increased at the operation side when the results were compared before the surgery at the same side and at the other side after the surgery. Also when we looked at the first and second masks which show the significant part of the stance phase; contact areas have similarly increased and the changes at the peak pressures were similar as contact areas. In both groups Harris Hip score was increased significantly after the operation. This is the first study to compare two different lateral approaches by pedobarographic analysis, clinical evaluation and functional scoring. The fuctional and clinical early results are similar in both lateral hip approaches for total hip arthroplasty when superior gluteal nerve protection, conjuant tendon repair and postoperative rehabilitation have done well. [Med-Science 2019; 8(1.000): 1-6]